Chase Corp: Force or Farce? - Marriage, Guy (Architectural History Aotearoa, 2009)
During the 1980s, one company grew to symbolise New Zealand’s unhealthy obsession with money. Chase Corporation appeared as the pinnacle of the New Zealand dream – tall buildings, high finance, the sky was the limit. At last we were joining the big time. The mantra "Greed is Good" was taken to heart in New Zealand, by architects, developers, and much of the public – at least in Auckland and Wellington. Glittering towers of mirrored glass appeared weekly in the press, promising to change the face of the city forever. The reality was different: poorly designed, badly built buildings were financed by shady deals, and heritage was destroyed casually, with little thought for the consequences. This paper will attempt to unravel some of the work undertaken by Chase Corp during the 1980s.